MENINGKATKAN KEMAMPUAN SISWA DALAM MENENTUKAN PECAHAN SENILAI MELALUI MEDIA PERMAINAN KARTU DOMINO - Suwasi'ah (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2019)
This study describes the role of teachers in improving the ability to determine the worth fractions in elementary students by using domino card game media. This type of research is classroom action research. The approach taken is a qualitative approach. The results showed a change in students abilities for the better. In the pre-cycle activities there are still many students who don’t understand the purpose of the worth fractions. After being given dominoes media and sample, capacity building is shown in learning cycle one. Four children from all students have started to be able to determine the worth fractions. This was repeated even experienced an increase in learning cycle two. Nearly three-fourths of the students in 4th grade are able to determine worth fractions, while the rest reach the KKM limit. The conclusion of this study is that dominoes media can be used to improve the ability to determine worth fractions in elementary students.